Correction: New remains of Stegodon zhaotongensis (Proboscidea, Stegodontidae) from the Late Miocene site of Shuitangba, Yunnan Province, China - William J. Sanders; Xue-Ping Ji; Nina G. Jablonski (Journal of Mammalian Evolution, 2026)

New finds of Ancylotherium hennigi (Mammalia, Perissodactyla, Chalicotheriidae) from the Plio-Pleistocene of Laetoli, Tanzania - Terry Harrison; Amandus Kwekason (Journal of Mammalian Evolution, 2026)

The neglected Reinhardt’s glyptodontine from Lagoa Santa, Brazil: a reassessment of taxonomic status and description of a new species of Glyptotherium - Édison Vicente Oliveira; Kasper Lykke Hansen; Kleberson de Oliveira Porpino (Journal of Mammalian Evolution, 2026)
This study reexamines a glyptodontine skull, NHMD 2045557, from Lagoa Santa, Brazil. Initially misidentified as the type of Hoplophorus euphractus by J. Reinhardt, it was later referred to Glyptodon clavipes. This identification remained unchallenged for decades. Recent comprehensive revisions of glyptodontines from northeastern and southeastern Brazil have prompted a reevaluation of the Lagoa Santa material. Currently, it is referred to as Glyptotherium sp., or tentatively, as Glyptotherium cf. cylindricum , a species originally described from Mexico that is also found in Central and North America. However, even if the generic assignment to Glyptotherium is accepted, the specific identity of the Brazilian material remains unresolved. To address this issue, we conducted an exhaustive review of the historical literature, beginning with the foundational works of Lund, Reinhardt, and Winge. We also reexamined the skull NHMD 2045557. Although Lund collected this specimen, Reinhardt first described and illustrated it in 1875 as “ Schistopleurum euphractum ” to replace Hoplophorus euphractus . We argue that Reinhardt misidentified the skull as the type of Hoplophorus euphractus , which invalidates the combination “ Schistopleurum euphractum ”. According to the ICZN, the name-bearing type of H . euphractus fixes the application of the name (Art. 70). Thus, Reinhardt’s classification constitutes a misidentification rather than a taxonomic revision of the original species. Therefore, we propose a new species of Glyptotherium for the aforementioned skull, described as Glyptotherium deuterophractum sp. nov. Comparative analyses with other glyptodont species reveal a distinctive combination of cranial, dental, tarsal, and osteodermal characteristics that distinguish the Brazilian and Venezuelan material from Glyptotherium texanum (from the Pliocene and Early Pleistocene of Central America, Mexico, and the southern United States) and from Glyptotherium cylindricum (Late Pleistocene of Panama, Guatemala, Mexico, and the southern United States).